High-Efficiency Integrated Color Routers by Simple Identical Nanostructures for Visible and Near-Infrared Wavelengths - Rongxuan Zhong; Xiayuan Xu; Yongle Zhou; Haowen Liang; Juntao Li (Photonics, 2023)
Imaging in both the visible and the near-infrared ranges has various applications in computational photography and computer vision. Comparing it with the traditional imaging system, integrating pixel-level metasurfaces on the imaging sensor is effective to plot the route of visible and near-infrared light to the right pixels, while the previously reported nanostructures were complicated to design and fabricate. Here, a pixel-level color router based on metalens, which provides a much simpler construction to improve the visible and near-infrared imaging efficiencies to 59% and 60%, is designed.